Religion, Belief and Medial Layering of Communication: Perspectives from Studies in Visual Culture and Artistic Productions Journal for Religion, Film and Media - Sigrid Schade (Journal for Religion, Film and Media, 2015)
The paper analyses the relationship between religious practices, belief and the media based on the medial layering of communication. The arguments are situated within the fields of studies in visual culture and cultural studies, reflecting on the role of art as a specific medium in the Western religious tradition. Vera Frenkel's video This Is Your Messiah Speaking (1990) is reviewed as a critical inquiry into religious practices and the media structures of communication.